2021
DOI: 10.3390/biom11020323
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Biochemical Pathways of Catalpol in Alleviating Diabetes Mellitus and Its Complications

Abstract: Catalpol isolated from Rehmannia glutinosa is a potent antioxidant and investigated against many disorders. This review appraises the key molecular pathways of catalpol against diabetes mellitus and its complications. Multiple search engines including Google Scholar, PubMed, and Science Direct were used to retrieve publications containing the keywords “Catalpol”, “Type 1 diabetes mellitus”, “Type 2 diabetes mellitus”, and “diabetic complications”. Catalpol promotes IRS-1/PI3K/AKT/GLUT2 activity and suppresses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 122 publications
1
20
0
Order By: Relevance
“…e precursor peptide source of apelin is composed of 77 amino acid residues, and the C-terminal of its carboxyl group is a synthetic peptide sequence that can be decomposed by peptidase into a variety of mature apelin active peptides, including apelin- 10, 11, 12, 13, 15, 17, 19, 28, 36, etc., of which apelin-13 has the strongest biological activity [8]. Studies have shown that apelin-13 can improve heart failure, pulmonary hypertension, pancreatic injury, etc., and can also protect neurovascular injury and relieve pain [9][10][11]. Studies have also shown that apelin-13 is closely related to obesity, but its specific mechanism is not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…e precursor peptide source of apelin is composed of 77 amino acid residues, and the C-terminal of its carboxyl group is a synthetic peptide sequence that can be decomposed by peptidase into a variety of mature apelin active peptides, including apelin- 10, 11, 12, 13, 15, 17, 19, 28, 36, etc., of which apelin-13 has the strongest biological activity [8]. Studies have shown that apelin-13 can improve heart failure, pulmonary hypertension, pancreatic injury, etc., and can also protect neurovascular injury and relieve pain [9][10][11]. Studies have also shown that apelin-13 is closely related to obesity, but its specific mechanism is not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that the TGF‐β signaling pathway plays an important role in the development of insulin resistance and obesity [3739]. CD109, an upstream factor of TGF‐β/Smad2/3, is important for attenuating diabetic renal fibrosis through inactivation of the TGF‐β/Smad2/3 pathway, and could be a new therapeutic approach for diabetic nephropathy [40]. In the present study, we found for the first time that the expression of CD109 protein was significantly lower in the placental tissue and early pregnancy plasma of patients with GDM, and may therefore be a potential predictive biomarker for GDM.…”
Section: Discussionmentioning
confidence: 99%
“…The process of skeletal muscle myogenesis is closely regulated by myogenic regulatory factors (MRFs), which means that muscle protein synthesis is inseparable from that ( Kevin et al, 2012 ; Zammit, 2017 ; Hwang et al, 2019 ). MyoD is a myogenic regulatory factor that can activate the myogenic differentiation program along with the downstream myogenin ( MyoG ) ( Zammit, 2017 ; Bhattamisra et al, 2021 ). Previous studies indicated that folic acid increased the mRNA expression of MRFs and induced the myogenic differentiation in C2C12 cell ( Hwang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%